TAUHID DAN DALIL WUJUD TUHAN PENDEKATAN DALIL NAQLI & AQLI - Muhammad Tahir Alibe (LP2M Universitas Ibrahimy, 2022)
This article discusses the concept of monotheism and the proposition of God's existence with the naqli & aqli propositional approach. The arguments in the rules of ushul consist of naqli arguments (al-Qur'an and Hadith) and aqli arguments (reason). The article shows that the concept of divinity is not built without a foundation, but is based on propositions. This type of research is qualitative with theological and philosophical approaches. Theological approach is used to complete a discussion based on the text. The results of this study indicate that the concept of monotheism and the proposition of the existence of God is obtained from the arguments, both from the naqli argument and the aqli argument. Therefore, belief in the existence of God is argumentative and rejects atheism, which denies the existence of God in the creation of the universe. Tawhid means the essence, nature and af'al of Allah is a unity that is not separate. The concept of monotheism is different from the view of monotheism which is generally understood.